Poland's long-term competitive position from the perspective of WEF global competitiveness reports - Stanisław Flejterski; Magdalena Majchrzak (Comparative Economic Research. Central and Eastern Europe, 2018)
Competitiveness is not clearly defined and there are different methods of measuring it. Analysis of the level of competitiveness on a macro scale is of interest to many entities. Competitiveness rankings are published in the Global Competitiveness Report prepared by the World Economic Forum (WEF), among others. 137 countries have been included in the WEF's 2017-2018 Report. A country's position in this ranking depends on many factors, classified in 12 pillars. In the group of 10 countries with the highest ranking, there are changes in order compared to the previous year, but the composition of this group did not significantly change. In this ranking, Poland was 39th. This is relatively high compared to 2008, in which it ranked 53rd out of 134 countries. In the future, further growth of the competitiveness of the Polish economy may depend on, among other things, the professionalism of managerial staff and on the shift to product competitiveness. It is also necessary to share knowledge between the university and the business sectors and between companies themselves.
Keywords: O17; P50; 330; global competitiveness; competitiveness report; World Economic Forum; ranking